2014
DOI: 10.1093/jncimonographs/lgu034
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Mind-Body Therapies to Individual Needs: Patients’ Program Preference and Psychological Traits as Moderators of the Effects of Mindfulness-Based Cancer Recovery and Supportive-Expressive Therapy in Distressed Breast Cancer Survivors

Abstract: Patients' program preference and baseline psychological functioning, rather than personality, were predictive of program benefits. These results suggest incorporating program preference can maximize the efficacy of integrative oncology interventions, and emphasize the methodological importance of assessing and accommodating for preferences when conducting mind-body clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 20 publications
2
62
0
Order By: Relevance
“…This could, on the other hand, also suggest a possible bias, namely, that patients willing to participate in RCTs are also those who are likely to benefit, even when baseline symptoms are minimal, especially when self‐referral sampling strategies are used . In terms of clinical practice, this could indicate that patients with a preference for MBIs are also those who should be referred to MBIs, which is in accordance with research suggesting that patients benefit more when they receive their preferred treatment …”
Section: Discussionsupporting
confidence: 70%
“…This could, on the other hand, also suggest a possible bias, namely, that patients willing to participate in RCTs are also those who are likely to benefit, even when baseline symptoms are minimal, especially when self‐referral sampling strategies are used . In terms of clinical practice, this could indicate that patients with a preference for MBIs are also those who should be referred to MBIs, which is in accordance with research suggesting that patients benefit more when they receive their preferred treatment …”
Section: Discussionsupporting
confidence: 70%
“…Thus, its positive results in improving cancer-related fatigue and quality of life measures cannot directly be extrapolated to other nongynecological cancers. Two other trials examining the effects of multimodal complementary treatments similar to ours, but conducted in breast cancer patients or breast cancer survivors only, also showed a positive effect of such programs on cancer-associated quality of life [34,35] . Hence, while the data of the present trial are consistent with previous studies on multimodal complementary medicine programs, they also illustrate that a broader and more diverse range of patients and cancer entities can benefit from the positive effects of such a treatment program.…”
Section: Discussionsupporting
confidence: 69%
“…In that large randomized clinical trial we demonstrated that while both active interventions were better than usual care, MBCR was superior to SET over a wide range of outcomes 7,8 , and benefits persisted over a full year of follow-up 9 . We also found that treatment preference at baseline had an effect on outcomes, in that those women who were assigned to their chosen intervention (MBCR, SET or the control condition) improved more over time on quality of life (QL) and stress symptoms than those who did not receive their preferred treatment 8 . Similarly, a systematic review on the influence of preference on clinical outcomes in acupuncture trials reported that preference was associated with reduced program attrition, with most studies demonstrating an effect of preference on outcome, though few were clinically significant 10 .…”
Section: Introductionmentioning
confidence: 83%